“Subdue” and “Have Dominion” Over The Earth: The Problem of Meaning - Ehusani, Richard (International Journal of Research in Interdisciplinary Studies, 2025)
The field of eco-theology has largely shaped itself as a response to the accusations that Christianity and the Bible laid the foundations for the development of exploitative modes of science and technology. Based on Genesis 1:28 where God commands humanity to subdue the earth and have dominion over all living creatures, ecologists, nature writers, and environmentalists assert the ecological culpability of a biblically inspired attitude of dominion over nature and reject the Bible as a relevant resource in the development of a sound environmental ethic. Such reading of the Bible and our increasing ecological problems prompt the following questions: Is it possible that the Bible is not as anthropocentric as it is presumed? Could its seeming anthropocentric outlook be revealing of the limitations of a particular historical culture? What is the intended meaning of the command words, “subdue” and “have dominion,” as used in the creation story in Genesis? This paper is an inquiry into the meaning of human dominion over the earth. Guided by the above questions, it explored biblical scholarship from the early Church Fathers and medieval theologians and reflected on the ethical concerns about planet Earth in Laudato si. The common persuasion running through these sources is that human dominion over the earth is not given for uncontrolled exploitation and destruction of nature. Beyond the literal interpretation of Genesis 1:28, there is a theology of human dependence in the creation account(s) that seems conveniently left out. Our ecological realities today require a more holistic approach to the study of scripture, towards promoting commitment to solidarity with humans and the earth’s other-kind, and for an all-encompassing global common good.